Civic Education Efforts in Cultural Aspects for the Formation of Student Identity - Eriza Zuhry, Fadya; Aulia, Hilda; Nasywa Zulfita; Rouli Margaretha; Matang, Matang; lham Hudi (Jurnal Edukasi Terkini, 2024)
We expect that using culture to shape students' identities as part of citizenship learning will result in students who are optimistic and possess a strong identity. Culture plays an important role in the formation of citizens who have a strong identity. This is done by strengthening Indonesian citizens who are religious, obey the law, maintain peace between religious communities, interact with people from various cultures, build social relationships, and feel proud as democratic and responsible citizens. We provide students with the opportunity to learn and apply diverse cultures, fostering the development of more tolerant characters in the future. This study confirms that students in citizenship learn to form strong identities and characters.